Analisis Return on Assets, Return on Equity, dan Net Profit Margin terhadap Kinerja Keuangan - Ela Melinda; Moch Fahru Komarudin (AKUNTANSI 45, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on the financial performance of PT Swontech in 2021-2025. The study is motivated by the importance of profitability ratios as indicators for assessing the effectiveness of asset management, equity utilization, and operational activities. This research employed a quantitative approach with an associative research design. Secondary data were collected from PT Swontech's financial statements for the period 2021–2025. Data collection was conducted through documentation techniques, while data analysis utilized descriptive and correlation analyses to examine the relationships among variables. The results indicate that an increase in ROA from -11.39% to 1.48%, ROE from -18.03% to 2.93% and NPM from -7.22% to 0.76%. The findings confirm that all research hypotheses were accepted, indicating that ROA, ROE, and NPM, both partially and simultaneously, positively influence the financial performance of PT Swontech. These findings support profitability theory and provide practical implications for management in improving the efficiency of asset utilization, equity management, and profit generation.